Characterization of the reniform nematode genome by shotgun sequencing - Nyaku, S.T.; Sripathi, V.R.; Kantety, R.V.; Cseke, S.B.; Buyyarapu, R.; Mc Ewan, R.; Gu, Y.Q.; Lawrence, K.; Senwo, Z.; Sripathi, P.; George, P.; Sharma, G.C. (Genome, 2014)
The reniform nematode (RN), a major agricultural pest particularly on cotton in the United States, is among the major plant-parasitic nematodes for which limited genomic information exists. In this study, over 380 Mb of sequence data were generated from pooled DNA of four adult female RNs and assembled into 67 317 contigs, including 25 904 (38.5%) predicted coding contigs and 41 413 (61.5%) noncoding contigs. Most of the characterized repeats were of low complexity (88.9%), and 0.9% of the contigs matched with 53.2% of GenBank ESTs. The most frequent Gene Ontology (GO) terms for molecular function and biological process were protein binding (32%) and embryonic development (20%). Further analysis showed that 741 (1.1%), 94 (0.1%), and 169 (0.25%) RN genomic contigs matched with 1328 (13.9%), 1480 (5.4%), and 1330 (7.4%) supercontigs of Meloidogyne incognita, Brugia malayi, and Pristionchus pacificus, respectively. Chromosome 5 of Caenorhabditis elegans had the highest number of hits to the RN contigs. Seven putative detoxification genes and three carbohydrate-active enzymes (CAZymes) involved in cell wall degradation were studied in more detail. Additionally, kinases, G protein-coupled receptors, and neuropeptides functioning in physiological, developmental, and regulatory processes were identified in the RN genome. © 2014 Published by NRC Research Press.
Keywords: 454 sequencing; Detoxification genes; Nematode parasitism genes; Reniform nematode